Les déterminants de la construction et de la mise en œuvre de démarches d’investigation chez deux enseignants de physique-chimie au collège - Alain Jameau; Jean-Marie Boilevin (Recherches en Éducation)
This paper examines the determinants of teacher’s action during the construction and implementation of an inquiry-based science education (IBSE). We study the case of two teachers, in the context of the teaching of mechanics in grade 9 in France. Our theoretical approach refers to science education and professional didactics. We have developed a specific methodology which one of the principles is monitoring teachers for two consecutive years, which includes their activity outside the classroom. We identify the determinants by analyzing the goals of teachers during their activity and the resulting tasks for students. We rely for this on a tracking criteria used by teachers to build an inquiry-based sequence. We show that different elements involved in the determinants of action: some categories of professional knowledge including PCK but also knowledge of teachers on how students learn science, the history of learning built in a class, on the epistemology of the discipline taught.